Observations of youth football training: How do coaches structure training sessions for player development? - O`Connor, D.; Larkin, P.; Williams, A. M. (Journal of Sports Sciences, 2018)
We used systematic observation tools to explore the structure (i.e., activity and inactivity) and sequencing (i.e., the types of activities used) of football coaching sessions in Australia following the implementation of a new National Curriculum. Youth soccer coaches (n = 34), coaching within the Skill Acquisition (U11-U13 n = 19) and Game Training (U14-U17 n = 15) phases of the Football Federation Australia National Curriculum participated. Participants were filmed during a regular coaching session, with systematic observation of the session undertaken to provide a detailed analysis of the practice activities and coach behaviours. Findings indicated a session comprised of Playing Form activities (40.9%), Training Form activities (22.3%), inactivity (31%), and transitions between activities (5.8%). Coaches prescribed more Training Form activities (e.g., individual (5.4%) and drills (15.1%)) early in the session and progressed to Playing Form activities (i.e., small-sided games (15.3%) then larger games (24.8%)) later in the session. Most inactivity reflected the players listening to the coach - either in a team huddle (9.9%) or frozen on the spot during an activity (16.5%). In addition, coaches generally spent over 3 min communicating to players prior to explaining and introducing an activity regardless of when in the session the activity was scheduled.